New age of partnership process - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
The long-term process of partnership building started by CTA in 1996 is now taking on a definite shape. Many organisations with whom CTA is in contact belong to the public sector. Nonetheless, as a result of the changes taking place in civil society...